Microbial Safety of Wood in Contact with Food: A Review. Issue 3 (26th February 2016) - Aviat, Florence; Gerhards, Christian; Rodriguez‐Jerez, José‐juan; Michel, Valérie; Bayon, Isabelle Le; Ismail, Rached; Federighi, Michel
Abstract: Food packaging is multifunctional: it protects from harvest to table. Four main groups of materials for direct food contact are mentioned in the literature: wood, glass, plastic, and metal. In this review, the focus is on wooden packaging for direct contact with food. In Europe, wood as a food contact material is subject to European Regulation (EC) No 1935/2004 states that materials must not transfer their constituents to food. Today, wooden packaging, like other packaging materials, does not have a Europe‐wide harmonized specific regulation, so member countries legislate at different levels. Wood has been safely used for centuries in contact with food but is usually questioned because of its microbiological behavior compared with smooth surfaces. Based on a review of published conclusions from scientific studies over the last 20 y and after a description of the general properties of wooden packaging, we focus on the microbiological status of natural wood. Then, we discuss the parameters influencing the survival of microorganisms on wood. Finally, we report on the transfer of microorganisms from wood to food and the factors influencing this phenomenon. This review demonstrates that the porous nature of wood, especially when compared with smooth surfaces, is not responsible for the limited hygiene of the material used in the food industry and that it may even be an advantage for its microbiological status. In fact, its rough or porous surface often generates unfavorable conditions for microorganisms. In addition, wood has the particular characteristic of producing antimicrobial components able to inhibit or limit the growth of pathogenic microorganisms.